Focal nodular hyperplasia and hepatocellular adenoma: The value of shear wave elastography for differential diagnosis. Issue 11 (November 2015) - Brunel, Thomas; Guibal, Aymeric; Boularan, Camille; Ducerf, Christian; Mabrut, Jean-Yves; Bancel, Brigitte; Boussel, Loïc; Rode, Agnès
Highlights: Shear wave elastography during ultrasound examination. Differences in stiffness between focal nodular hyperplasia and hepatocellular adenoma. Avoiding invasive procedure for differential diagnosis. Additional diagnostic tool for differential diagnosis between these two benign hepatic lesions. Abstract: Objective: This study assessed the clinical usefulness of shear wave elastography (SWE) during ultrasound for differentiating between focal nodular hyperplasias (FNHs) and hepatocellular adenomas (HAs). Materials and methods: SWE was performed on 56 patients presenting with 76 liver lesions (57 FNHs and 19HAs) that were confirmed by MRI and contrast-enhanced ultrasound (CEUS) ( n  = 55) or by histology ( n  = 21). A mean elasticity value was obtained for each lesion. The ratios of the elasticity of the lesions to the elasticity of the surrounding liver were determined. The optimal elasticity cut-off value for distinguishing between the two lesion types was determined using ROC analysis. All lesions that were classified as "undetermined" after CEUS were reclassified using the elasticity values. Results: The mean elasticity value was 46.99 ± 31.15 kPa for FNHs and 12.08 ± 10.68 kPa for HAs ( p  < 0.0001). The mean relative elasticity ratio values were 7.94 ± 6.43 and 1.91 ± 1.70, respectively ( p  < 0.0001). The ROC analysis showed a maximal accuracy of 95% for identification with a cut-off of 18.8 kPa for lesion elasticity (accuracy of 96% with a cut-off of 1.98 for the relative elasticity ratio). A total of 68CEUS were performed, and 17 lesions (25%) were classified as "undetermined" after CEUS. With these cut-off values 16 lesions (94.1%) were correctly reclassified as FNHs. Conclusion: SWE is a useful adjunctive tool for differentiation between FNH and HA during ultrasound examination.